Prevalence of unrepaired third- and fourth-degree tears among women taken to the operating room for repair of presumed obstetric fistula during two fistula camps in Kenya. Issue 3 (March 2016) - Lozo, Svjetlana; Eckardt, Melody; Altawil, Zaid; Nelson, Brett; Ahn, Roy; Khisa, Weston; Burke, Thomas
Abstract Introduction and hypothesis More than 2 million women on earth today are said to be suffering from obstetric fistula (OF), a communication between the vagina and either the urinary tract or rectum. Since unrepaired third- and fourth-degree perineal tears often manifest with symptoms identical to OF, we hypothesized that the global burden of OF is in part due to these unrepaired deep obstetric tears. Methods Four consultant gynecologists retrospectively reviewed the medical and operative records of all obstetric fistula cases that underwent surgical repair during the July and August, 2014, Kenyatta National Hospital and Embu Provincial Hospital Fistula Camps in Kenya. Results One hundred and eighty charts were reviewed. All 180 women had fecal incontinence (FI), urinary incontinence (UI), or both as their primary complaint. Sixty of the 180 (33 %) women had isolated FI as their presenting symptom, and at operation, 57 of these 60 (95 %) were found to have unrepaired third- and fourth-degree obstetric tears. Ninety-two of the 180 (51 %) women with OF symptoms ultimately had true OF confirmed at operation. Conclusion These findings suggest that many women with OF symptoms in Kenya may harbor unrepaired third- and fourth-degree tears. Additionally, women with isolated FI may be more likely to suffer from third- and fourth-degree tears than from true OF. Immediate postpartum diagnosis and repair of third- and fourth-degree perineal tears could significantly reduce the overall burden of women with symptoms of OF.